Kenya agricultural research strategy and plan volume 2: Priorities and programs - International Service for National Agricultural Research (International Service for National Agricultural Research, 1985)
It is widely accepted that no agricultural research system in any country, however well funded and organized, can attempt to solve all the problems affecting agricultural production; certainly not in a developing country such as Kenya, where there is a mosaic of different agro-ecological zones, a limited area of high- and medium-potential land, rapid degradation of resources in the semi-arid and arid areas, a changing agricultural tenure situation, and a very rapidly increasing population. Under these circumstances, priorities for agricultural research must be established and available resources allocated to the solution of those problems that will contribute most to the overall development objectives of the nation.